Contract facing the unforeseeability in French-speaking countries of sub-Saharan Africa: essay on a socio-economic normative analysis - (:unkn) unknown (My University, 2023)
In contrast to the original african laws, the modern african laws, as inherited from colonization, have difficulty to meet the yearning of contemporary african societies for a minimum of ‘’normativization’’ of social relationships. The judge’s refusal to adapt an imbalanced contract, following unforeseeable circumstances change in the civil law of the French-speaking countries of Africa South of the Sahara resulting from the mimicry of the French Civil Code of 1804, is evidence of...
Keywords: African Research